Instruments to evaluate the leadership in captains of sport teams(Original) (Revista científica Olimpia, 2020)
The article that is exposed is part of a thesis of master of Psychology of the Sport, which is studied at the moment in the University of Granma, with headquarters in the Ability of Physical Culture of Santiago from Cuba. In the same one it is stood out the importance of the diagnosis and the necessity of a correct selection and application of the instruments to guarantee the objectivity of you results. In the case peculiar of this investigation the problem to solve is how to contribute to the improvement of the leadership in the sport team captains? , thematic current in the formation of athletes in Cuba, as long as it is the directive interest that these not alone they are formal leaders but rather they also fulfill the qualities that characterize to the natural ones guaranteeing that they develop an active list in the training and the competitions demonstrating in these spaces a capacity movilizativa, being emphatics, creative, agglutinants, optimist, among others. It is for it that during this stage of the investigation the objective is summed up in characterizing the current state of the leadership of the captain of the team of feminine Volleyball, school category of the EIDE "Captain Acosta" of Santiago from Cuba. The selected sample is already the mentioned sportsman, and the 13 members of the team, considered all for the age like adolescents. The application of an appropriate diagnosis will guarantee a correct selection of the captains of sport teams, and with the obtained results they will be been able to solve the problems that exist in those that act as such.
Keywords: diagnostic; leadership; captain; sport team